STORY RELATED TO RAMA IN DIFFERENT STYLES IN RAJASTHAN PAINTING STYLE - Sharma, Rajni; Premlata (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The story of Rama in the Mewar style of painting of Rajasthan has attracted the attention of many critics and reviewers. The illustrated Rama manuscripts prepared at the end of the period of Rana Jagat Singh of Mewar (1628-52) have been important not only for him but for more than 400 paintings. The famous scholar 'Goetz' does not consider these paintings to have any signs of the new style (Yug Art) but on the contrary, he has considered this style to be completely of the old style and these manuscripts to be depicting a long and highly developed tradition. They establish a harmony between the early Mewar style and the famous style of Jagat Singh's period. The Mewar style is visible in the sculptures and paintings of the 16th to 17th centuries. Dr. Sharma has considered the influence of Mughal style on the costumes and ornaments by giving examples of chokdar agarkhana jama, transparent sari, nose pin and armor etc. used in the paintings of Aranyakand. He has considered Ravana, who appears in disguise, to be a Muslim fakir instead of a saint. Similarly, Ram, who is fighting against Ravana's army, appears to be a Mughal soldier instead of a Rajput warrior. And all the miniature paintings of Arsha Ramayana are considered by many scholars to reflect Mughal influence and Apabhramsha style. Two Indian components, Persian element and European realism, have been important in the creation of Mughal style. The painters of Ramayana paintings, Manohar and Sahibdin, were the main painters of the period of Maharana Jagat Singh I (1628-52). And the credit of painting the main text of his time, 'Arsha Ramayana', also goes to these two artists. Shmotchandra has acknowledged the influence of Mughal art in the depiction of figures and architecture of all the Ramayana paintings, “according to Lasti's opinion, which reminds of Manohar. In such paintings, the mythological literature Ramayana and Mahabharata and the devotion and romance kept in the medieval period have been greatly enhanced by the literature of Ram. Hence, in the Arsh Ramayana written by Maharishi Valmiki in 1649 AD to 1653 AD, the various incidents related to the life of Ram have been depicted in these paintings in different ways and the artistic and aesthetic importance of the paintings have been presented before the art critics.